PENGGUNAAN STRATEGI TEAMS GAMES TOURNAMEN (TGT) UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI PADA POKOK BAHASAN PASAR KEUANGAN UNTUK SISWA KELAS XI IPS SMA NEGERI 1 RUMBIO JAYA - Mahful Mahful (Perspektif Pendidikan dan Keguruan, 2014)
This reserach was done based on the preliminary observation in the researher class XI IPS at SMA Negeri 1 Rumbio Jaya. The researcher did tests to the students as much as 25 items, students got difficulties in comprehending the material. As many as 88% students made mistakes in answering questions. They got score below tahn 75, so it did not reach the minimum completeness criteria (KKM); over 75. Only 12% of students were able to answer questions. Their difficulty in answering the question because they were not full attention when learning in the classroom. The researcher implemented Teams Games Tournament to motivate students by applying Classroom Action research the result of students based on the analysis data, the problems shown in the learning process was primarily the result of economic study on the subject of the financial markets for students of class XI IPS SMAN 1 Rumbio Jaya improved by usingthe strategy of Teams Games Tournamen (TGT) t and it had shown satisfactory results.